The case for structured markets in Malawi - Gondwe, Anderson; Baulch, Bob (International Food Policy Research Institute, 2017)
After reviewing Malawi’s recent export experience, this policy note examines the types and potential contributions of structured markets to export marketing with a specific focus on commodity exchanges and export mandates. An export mandate means that a commodity cannot be exported except via a structured market.